Separation of single-walled carbon nanotubes using aqueous two-phase system - Tang, Malcolm S. Y.; Show, Pau Loke; Yu, Kiat Lin; Woon, Kai Lin; Tan, Chin Ping; Ling, Tau Chuan (Elsevier, 2014)
The separation of metallic single-walled carbon nanotubes (M-SWCNTs) from semiconducting single-walled carbon nanotubes (S-SWCNTs) in as-received SWCNTs is an important step to integrate carbon nanotubes into electronic applications. In this study, the effect of molecular weight (Mw) of polyethylene glycol (PEG) on the separation of M-SWCNTs from as-received SWCNTs using aqueous two-phase system (ATPS) consist of PEG, dextran, organic solvent N-methylpyrrolidone (NMP) and water has been investigated. PEG with Mw 6000 and 10,000 showed higher partition coefficient (K) and yield (Y). The semiconducting single-walled carbon nanotube (S-SWCNT) was attracted to the bottom phase. Varying the concentration of PEG 6000 and dextran could enrich the purity of M-SWCNT in the top phase to 0.2574 compared to the pristine value of 0.1506. The volume ratio (VR) that gave the highest enrichment of M-SWCNT is found to be 1.5. However, there was no significant changes in purification factor (PF) and purity when the concentration of NMP and water were manipulated. This finding provides a solid foundation for the studies of ATPS to separate different species of SWCNTs.